2014
DOI: 10.2147/dnnd.s57502
|View full text |Cite
|
Sign up to set email alerts
|

Axonal transport and neurodegenerative disease: vesicle-motor complex formation and their regulation

Abstract: The process of axonal transport serves to move components over very long distances on microtubule tracks in order to maintain neuronal viability. Molecular motors-kinesin and dynein-are essential for the movement of neuronal cargoes along these tracks; defects in this pathway have been implicated in the initiation or progression of some neurodegenerative diseases, suggesting that this process may be a key contributor in neuronal dysfunction. Recent work has led to the identification of some of the motor-cargo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 253 publications
(390 reference statements)
0
7
0
Order By: Relevance
“…This finding is consistent with a recent study of MAPT p.V337M-expressing cerebral organoids, where a loss of protein homeostasis was reported (Bowles et al ., 2021). Defects in endolysosomal pathways have been implicated in reduced clearance of protein and cell debris, which may contribute to neurodegeneration (Liu, Rizzo and Puthanveettil, 2012; Gunawardena, Anderson and White, 2014; Etchegaray et al ., 2016; Viegas, Estronca and Vieira, 2012; Kulkarni and Maday, 2018; Xu et al ., 2021). Thus, here, we identify a series of pathways that are common across different MAPT mutation types, suggesting that stem cell models capture defects observed in FTLD-tau patients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a recent study of MAPT p.V337M-expressing cerebral organoids, where a loss of protein homeostasis was reported (Bowles et al ., 2021). Defects in endolysosomal pathways have been implicated in reduced clearance of protein and cell debris, which may contribute to neurodegeneration (Liu, Rizzo and Puthanveettil, 2012; Gunawardena, Anderson and White, 2014; Etchegaray et al ., 2016; Viegas, Estronca and Vieira, 2012; Kulkarni and Maday, 2018; Xu et al ., 2021). Thus, here, we identify a series of pathways that are common across different MAPT mutation types, suggesting that stem cell models capture defects observed in FTLD-tau patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although very useful, they do not always reflect the clinical and pathological changes present in human subjects [37,38,40]. Many papers indicated that disorders in the intracellular transport might be crucial for the initiation or progression of motor neuron degeneration [35,41,42,43,44]. In our previous studies, we observed important changes in the expression of tau isoforms, kinesins and dynactin in various regions of the CNS obtained from autopsies of SALS patients and transgenic mice with symptoms of motor neuron degeneration [36,37,38,45].…”
Section: Discussionmentioning
confidence: 99%
“…DCTN3 (or p24) is the smallest (light) dynactin subunit, which is involved in protein-protein interactions and thus participates in the assembly of the dynactin complex [32]. There is an increasing number of reports that link defects in axonal transport with motor neuron degeneration [33,34,35]. …”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that TDP-43 may also be involved in the axonal transport defects seen in ALS [ 27 ]; axonal transport defects are commonly seen in neurodegenerative diseases [ 78 ]. TDP-43 has an important role in regulating axonal growth and impairment in posttranscriptional regulation of mRNAs in the cytoplasm of motor neurons [ 81 ]. Mutations in the genes coding for axonal transport first came to light when LaMonte et al showed that disruption of the dynein/dynactin interaction by postnatal overexpression of p50/dynamitin, a 50-kDa subunit of dynactin encoded by DCTN2 , caused reduced axonal transport in motor neurons and consequently led to a late-onset progressive motor neuron disease phenotype in the transgenic mice [ 82 ].…”
Section: Mechanism and Molecular Pathology Of Als And Ftldmentioning
confidence: 99%